2017
DOI: 10.1093/annonc/mdx355
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoural evolutionary landscape of high-risk prostate cancer: the PROGENY study of genomic and immune parameters

Abstract: BackgroundIntratumoural heterogeneity (ITH) is well recognised in prostate cancer (PC), but its role in high-risk disease is uncertain. A prospective, single-arm, translational study using targeted multiregion prostate biopsies was carried out to study genomic and T-cell ITH in clinically high-risk PC aiming to identify drivers and potential therapeutic strategies.Patients and methodsForty-nine men with elevated prostate-specific antigen and multiparametric-magnetic resonance imaging detected PC underwent imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…As such, it is not clear that preclinical models are representative of the low to intermediate risk cancers included in this study . Furthermore, it is worth noting that many tissue samples analyzed as part of this trial had minimal to no tumor content because of the low‐grade nature of many of these cases, which could further impact the degree of inflammation present in the samples that were analyzed . Interestingly, our group has previously shown that there are significantly more tumor‐infiltrating lymphocytes (TIL) in the small subset of PC cases with mismatch repair deficiency, with a linear relationship between TIL density and mutational load .…”
Section: Discussionmentioning
confidence: 98%
“…As such, it is not clear that preclinical models are representative of the low to intermediate risk cancers included in this study . Furthermore, it is worth noting that many tissue samples analyzed as part of this trial had minimal to no tumor content because of the low‐grade nature of many of these cases, which could further impact the degree of inflammation present in the samples that were analyzed . Interestingly, our group has previously shown that there are significantly more tumor‐infiltrating lymphocytes (TIL) in the small subset of PC cases with mismatch repair deficiency, with a linear relationship between TIL density and mutational load .…”
Section: Discussionmentioning
confidence: 98%
“…Conceptually, heterogeneity encompasses multiple domains (e.g., spatial, temporal, and clonal) and can be applied to any measurable feature of a tumor; thus, it remains unclear exactly which molecular constituents of heterogeneity are most consequential to clinical outcomes. Previous studies of heterogeneity in other tumor types (e.g., renal, prostate, and lung) have focused primarily or exclusively on phylogenetic mutational analyses to characterize clonal heterogeneity of tumor cell content [29][30][31][32] . When performed, multiregion sequencing either for tumor cell mutations or TCR profiling has surveyed minimal numbers of regions (e.g., three to five per tumor), often in relatively small numbers of samples 31,[33][34][35] , whereas truly multi-platform analyses have effectively evaluated inter-tumoral rather than ITH 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Add to this challenge the variability in prostate cancer tumour attributesvolume, location, heterogeneity (genetic, radiological, and histological), degree of immune infiltrate, and the extent of microscopic extension, we begin to get the picture [1].…”
mentioning
confidence: 99%
“…Lymph node dissection during radical prostatectomy for prostate cancer: extending the template in the right patients without increasing complications I t took long time and consistent evidence to endorse the staging role of extended pelvic lymph node dissection (PLND) in prostate cancer (PCa). The poor performance of both conventional and functional imaging in identifying preoperative nodal status has contributed to making extended PLND the most accurate nodal staging procedure in PCa [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation